2022
DOI: 10.1093/nar/gkac844
|View full text |Cite
|
Sign up to set email alerts
|

rRNA expansion segment 7 in eukaryotes: from Signature Fold to tentacles

Abstract: The ribosomal core is universally conserved across the tree of life. However, eukaryotic ribosomes contain diverse rRNA expansion segments (ESs) on their surfaces. Sites of ES insertions are predicted from sites of insertion of micro-ESs in archaea. Expansion segment 7 (ES7) is one of the most diverse regions of the ribosome, emanating from a short stem loop and ranging to over 750 nucleotides in mammals. We present secondary and full-atom 3D structures of ES7 from species spanning eukaryotic diversity. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Previous studies suggested that expansion segments can serve as interaction platforms for ribosome-associated factors, binding with specific mRNAs, regulating translation fidelity, and controlling compartment-specific translation (145)(146)(147)(148)(149). ES7L, the largest eukaryotic expansion segment, contains a highly conserved core signature fold and long tentacle-like extensions that undergo rapid evolutionary changes (150). In yeast, the rRNA expansion segment ES7L was proposed to bind aminoacyl tRNA synthetases, potentially modulating translation efficiency (146).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that expansion segments can serve as interaction platforms for ribosome-associated factors, binding with specific mRNAs, regulating translation fidelity, and controlling compartment-specific translation (145)(146)(147)(148)(149). ES7L, the largest eukaryotic expansion segment, contains a highly conserved core signature fold and long tentacle-like extensions that undergo rapid evolutionary changes (150). In yeast, the rRNA expansion segment ES7L was proposed to bind aminoacyl tRNA synthetases, potentially modulating translation efficiency (146).…”
Section: Discussionmentioning
confidence: 99%
“…An evolutionary increase in rRNA size and complexity has most commonly been observed through the insertion of so-called expansion segments (ESs), GC-rich insertions of varying lengths into the rDNA sequence [ 18 ]. Guided by information from both high-resolution 3D and secondary structure modelling, a model has emerged, termed ‘the accretion model’, which implies a general tendency towards molecular growth, i.e., expansion, of rRNA [ 39 ]. According to its principles, rRNA expanded iteratively and incrementally in size during evolution without a substantial remodelling of the ribosome’s core or common trunk; as such, ES sites have increased as organisms became more complex.…”
Section: Ribosomal Rna Expansion Segmentsmentioning
confidence: 99%
“…According to its principles, rRNA expanded iteratively and incrementally in size during evolution without a substantial remodelling of the ribosome’s core or common trunk; as such, ES sites have increased as organisms became more complex. While most commonly observed in eukaryotes, ESs have been identified in the 5S rRNA of 36 bacterial strains and Archaea, which possess ESs with most insertions ranging between~5–20 nt in length at sites that coincide with those of eukaryotic ESs [ 18 , 39 ]. An exception to these short Archaeal ESs, are the Asgard ES39 and ES9, which have been discovered in the LSU rRNA Asgard archaeal phyla and, ranging in length from 50 to 200 nt, are closer to eukaryotic ESs, where ES39S varies between 80 nt in protists and 138 nt in S.cerevisiae to 178 nt in Drosophila and 231 nt in humans [ 40 ].…”
Section: Ribosomal Rna Expansion Segmentsmentioning
confidence: 99%
See 2 more Smart Citations